The Life and Fate of Mesenchymal Stem Cells - Eggenhofer, Elke; Luk, Franka; Dahlke, Marc H.; Hoogduijn, Martin J. (Frontiers in Immunology, 2014)
Mesenchymal stem cells (MSC) are present throughout the body and are thought to play a role in tissue regeneration and control of inflammation. MSC can be easily expanded in vitro and their potential as a therapeutic option for degenerative and inflammatory disease is therefore intensively investigated. Whilst it was initially thought that MSC would replace dysfunctional cells and migrate to sites of injury to interact with inflammatory cells, experimental evidence indicates that the majority of administered MSC get trapped in capillary networks and have a short life span. In this review we discuss current knowledge on the migratory properties of endogenous and exogenous MSC and confer on how culture induced modifications of MSC may affect these properties. Finally we will discuss how, despite their limited survival, administered MSC can bring about their therapeutic effects.